Peningkatan Kesadaran Kesehatan Pernapasan melalui Skrining Fungsi Paru dengan Spirometri di Kelurahan Tanjung Duren Selatan, Jakarta Barat - Ruslim, Daniel; Santoso, Alexander Halim; Gunaidi, Farell Christian; Soeltanong, Dianova; Lumintang, Valentino Gilbert (Jurnal Pengabdian Bidang Kesehatan, 2025)
Pulmonary function disorders are commonly underdiagnosed health issues, especially in urban areas with high air pollution and prevalent smoking habits. Early detection through spirometry plays a crucial role in the promotion and prevention of respiratory diseases such as asthma and Chronic Obstructive Pulmonary Disease (COPD). However, public awareness and access to spirometry remain limited, including in the Tanjung Duren Selatan subdistrict of West Jakarta. This community service program was conducted using the Plan-Do-Check-Act (PDCA) cycle management approach. The target population consisted of productive-age residents willing to participate in health education and lung function screening. Spirometry examinations were conducted alongside interactive counseling about respiratory health and risk factors. Evaluation was carried out through spirometry results and participant satisfaction surveys. A total of 92 participants took part in the activity, consisting of 70 females (76.1%) and 22 males (23.9%), with a mean age of 43.78 years (SD ±12.93). The average Vital Capacity (VC) was 2.26 L, Forced Vital Capacity (FVC) was 2.13 L, and Forced Expiratory Volume in 1 Second (FEV1) was 1.95 L. The mean FEV1/FVC ratio was 107.12%, with 100% of participants showing normal lung function. This activity demonstrates that spirometry is an effective tool for monitoring lung function and increasing community awareness. Similar screening initiatives should be expanded to support early detection of respiratory disorders at the community level.